2020
DOI: 10.1086/708856
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Communal Conflicts and Intergroup Lending

Abstract: We provide microeconomic evidence on the link between ethnic frictions and market efficiency, using dyadic data on managers and borrowers from a large Indian bank. Our analysis builds on the idea that exposure to religion-based communal violence may intensify branch managers' same-group preferences, and thus result in lending decisions that are more sensitive to a borrower's religion. We find that, in our sample of Hindu loan officers, those with substantial riot exposure prior to joining the bank lend relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 25 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Previous research primarily focuses on the origins of conflict (seeBlattman and Miguel, 2010, for a review) and its impact on growth (Rodrick, 1999), credit markets(Fisman et al, 2020), human capital(Miguel and Roland, 2011) and cooperation (seeBauer et al, 2016 for a review).…”
mentioning
confidence: 99%
“…Previous research primarily focuses on the origins of conflict (seeBlattman and Miguel, 2010, for a review) and its impact on growth (Rodrick, 1999), credit markets(Fisman et al, 2020), human capital(Miguel and Roland, 2011) and cooperation (seeBauer et al, 2016 for a review).…”
mentioning
confidence: 99%
“…While most of the literature focuses on the impact of direct exposure to violence, notable exceptions include the literature on the impact of refugees and displacement on destination communities (Calderón-Mejía and Ibáñez, 2015;Morales, 2018) and the spillovers of wars for frontier scientific activity (Iaria, Schwarz, and Waldinger, 2018). Most closely to our work, studies have shown that conflict may induce ethnic tensions which then reduces the productivity of inter-ethnic teams (Hjort, 2014) and increases discrimination in various critical institutions, such as banks (Fisman, Sarkar, Skrastins, and Vig, 2018), courts (Shayo and Zussman, 2011), and stock exchanges (Moser, 2012). We take this literature a step further and document that ethnic tensions also hurt trade.…”
Section: Introductionmentioning
confidence: 85%
“…In contrast, we argue that erosion of trust in enemy's institutions can be equally important-even if there is no decline in inter-ethnic trust, firms may become fearful that the opposite side of the conflict will stop enforcing trade contracts. In exploring this mechanism, we relate to the literature showing that conflict may lead to increased discrimination in various critical institutions, such as banks (Fisman et al, 2018), courts (Shayo and Zussman, 2011), and stock https://www.volyn24.com/news/96598-luckyj-zavod-kupuie-avtomobilni-detali-v-rosii-deputat). Another company faced pressure for producing buses with 95% of all inputs coming from Russia (https://tsn.ua/groshi/tenderniyskandal-ukrayina-zakupila-shkilni-avtobusi-u-virobnika-tehniki-dlya-armiyi-rf-713165.html).…”
Section: The Erosion Of Trust In Russian Institutionsmentioning
confidence: 99%
“…A student's higher environmental beliefs in terms of consumption and purchase behaviour also had a higher PIR score. Literature has shown that sociocultural attributes could lead to biased results of surveys [57][58][59][60][61]. Although socio cultural differences are assumed in research involving humans, the results can be interpreted wrongly if there is no comparability [57].…”
Section: Future Research Suggestionsmentioning
confidence: 99%